Tandem-L: A Highly Innovative Bistatic SAR Mission for Global Observation of Dynamic Processes on the Earth's Surface - Moreira, Alberto; Krieger, Gerhard; Hajnsek, Irena; Papathanassiou, Konstantinos; Younis, Marwan; Lopez-Dekker, Paco; Huber, Sigurd; Villano, Michelangelo; Pardini, Matteo; Eineder, Michael; De Zan, Francesco; Parizzi, Alessandro (IEEE Geoscience and Remote Sensing Magazine, 2015)
Tandem-L is a proposal for a highly innovative L-band SAR satellite mission for the global observation of dynamic processes on the Earth's surface with hitherto unparalleled quality and resolution. It is based on the results of a pre-phase A study which started in 2013 and is currently undergoing a phase-A study. Thanks to the novel imaging techniques and the vast recording capacity with up to 8 terabytes/day, it will provide vital information for solving pressing scientific questions in the biosphere, geosphere, cryosphere, and hydrosphere. By this, the new L-band SAR mission will make an essential contribution for a better understanding of the Earth system and its dynamics. Tandem-L will, moreover, open new opportunities for risk analysis, disaster management and environmental monitoring by employing especially designed acquisition modes and techniques in combination with a reconfigurable tandem satellite configuration and an L-band SAR instrument with advanced digital beamforming techniques.
DLR Import::2019-04-02